Social support groups and policy recommendations for managing type 2 diabetes: perspective of healthcare professionals in Ghana - Ahiale, Christine; Kumah, Augustine (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundOver the last decades, non-communicable diseases such as diabetes have remarkably increased due to rapid urbanization, unhealthy lifestyles, and ageing. The World Health Organization (WHO) indicates that the “diabetes epidemic” will continue in the coming decades, yielding enormous human and economic costs around the world. This study explores healthcare workers’ views on social support groups and policy recommendations for managing type 2 diabetes in Ghana.MethodThis study utilized a facility-based cross-sectional qualitative research design to explore healthcare workers’ views on social support groups and policy recommendations for managing type 2 diabetes in Ghana between January and May 2023. Health workers who worked in the three selected regional hospitals for at least one year and at the diabetic clinics of the three selected regional hospitals of the respective regions at the time of this study were included. The study used purposive sampling to select 12 health workers (Nurses) as key informants. One (1) facility head of each facility and three (3) health workers, each working in the diabetic clinic of each regional hospital, were selected for key informant interviews. The interviews were recorded and transcribed in English. Notes from the interview were transcribed after the key informant interview. Data was imported into the Nvivo 7 software. The results were presented as prose, analyzed, and discussed in themes.ResultsMajor challenges facing people living with diabetes were the cost of medication, limited NHIS coverage, frequent morbidity and the chronic nature of the disease, putting psychological pressure on the patients. The policy recommendation was on mass education and the expansion of NHIS coverage.ConclusionThe study has noted some significant challenges faced in managing type 2 diabetes mellitus in Ghana. Addressing the diabetes epidemic in Ghana requires a comprehensive and multi-pronged approach, focusing on prevention, early detection, access to care, and diabetes education. Implementing the policy recommendations outlined in this study can significantly improve diabetes management in Ghana, reduce the burden of the disease, and enhance the overall health and well-being of the population.